2008
DOI: 10.1002/jrs.1812
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate and amide III mapping in sialoliths with Raman microspectroscopy

Abstract: Sialoliths, a cause of the salivary gland infection, are reported to be composed of inorganic and organic substances. However, the precise mechanism of sialolith formation remains unclear. The purpose of this report is to elucidate this mechanism by analyzing the precise distribution of phosphate (an inorganic substance) and amide III (an organic substance) in sialoliths by using Raman microspectroscopy. Sialoliths from the submandibular gland duct were analyzed by this form of observation and by a scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Raman spectrum microscope (MRS-1000 MTS-model, JASCO Ltd. Co., Tokyo, Japan) was used for the measurement of Raman shift spectrum (Figure 5) and the mapping image (1.45×1.45 mm 2 ) on the cryo-sectioned slice of the raw tumor tissue of the model mouse at 2738 cm −1 peak area excited at 785 nm as same methods as reported by our previous reports [56, 57]. …”
Section: Methodsmentioning
confidence: 99%
“…Raman spectrum microscope (MRS-1000 MTS-model, JASCO Ltd. Co., Tokyo, Japan) was used for the measurement of Raman shift spectrum (Figure 5) and the mapping image (1.45×1.45 mm 2 ) on the cryo-sectioned slice of the raw tumor tissue of the model mouse at 2738 cm −1 peak area excited at 785 nm as same methods as reported by our previous reports [56, 57]. …”
Section: Methodsmentioning
confidence: 99%
“…The formation of stones in the salivary extraglandular system has been predominantly attributed to slow salivary flow, salivary stagnation, and intricate metabolic events (Waseem and Forte, 2005). Various studies (Kinoshita et al , 2008; Su et al , 2010; Ribeiro et al , 2011) have demonstrated the microstructure of sialoliths and features of electrolyte alteration in saliva during pathologic states; however, less attention has been paid to the macroscopic effects of changes in salivary flow. Using CFD, we explored the changes in the salivary flow field of Stensen’s duct, which we believe may affect the symptoms and prognosis of this pathologic condition.…”
Section: Discussionmentioning
confidence: 99%
“…These mineral components have been studied by various methods including high-resolution electron microscopy and X-ray diffraction. Kinoshita et al explained in detail the precise formation of sialolith by analyzing the actual distribution of organic (amide III) and inorganic (phosphate) content within the sialolith with the help of Raman spectroscopy (117). The sialolith from the submandibular gland was used for the study.…”
Section: Applications Of Raman Spectroscopy In Other Conditionsmentioning
confidence: 99%